Tonemski naglasni tipi glagola v (knjižni) slovenščini - Šekli, Matej (Jezikoslovni zapiski, 2005)
This article discusses the pitch accent classes of the verb in (standard) Slovene, from the diachronic as well as synchronic point of view. The synchronic perspective presents the accent paradigms of a single verb class. The diachronic point of view defines the Proto-Slavic origin of the single verb form. The discussion is based on (standard) language material. Dialectal material is adduced especially when being more archaic.
Keywords: Slovene; slovenščina; glagol; verb; naglas; tonemski naglas